PEMBINAAN TANGGUNG JAWAB WARGA NEGARA DALAM MEMECAHKAN MASALAH-MASALAH SOSIAL MELALUI PENDIDIKAN KEWARGANEGARAANKEMASYARAKATAN (COMMUNITY CIVICS) - Rohani (2013)
The study was initiated by the fact that the citizens' responsibility in keeping environment was still low. Thus, the responsibility guidance trough Civics in general and trough domain of curricular, academic, and socio-cultural in specific was required. In this study, Civics was examined from socio-cultural domain (Civics developed by social voluntary organization, mass media, and other civil society movements). The study intended to obtain factual description of the citizen responsibility guiding process in solving Kapuas river pollution trough community civics. The study used qualitative approach. It was designed as a case study. The data was obtained by employing four techniques: observation, interview, literature study, and documentation. The findings showed that citizen responsibility in community civics to solve social problems trough social voluntary organization in Pontianak was low without guidance. But after conducting guidance program, the citizen responsibility was appeared. Individuals joining to the environment-concerned voluntary organization showed high responsibility. In addition, ccommunity civics played important role in guiding citizens' responsibility. The procedures taken were: (1) continuous training, (2) discussion, (3) transect walk, and (4) direct practice of recycling. The study also recorded other organizations which took the role of citizens responsibility guidance in solving Kapuas river pollution; they are WahanaVisi Indonesia ADP Urban Pontianak, CahayaMaju, andRiakBumi. The guidance resulted on developing responsibility and care to environment, and altering society habits to be clean and healthy. The study gave recommendations to local government of Pontianak and related departments to socialize environment regulations regularly and to provide rubbish bins in the flood plain of Kapuas River. And it also recommended the environment-concerned voluntary organizations in Pontianak to increase their roles continuously in solving Kapuas River pollution. Key words: responsibility, citizen, Civics, community civics